“For those who don’t cry at night”: exploring narratives of integrative medicine practitioners treating hospital personnel during war - Schiff, Elad; Ben-Arye, Eran; Stoffman, Gali; Popper-Giveon, Ariela; Keshet, Yael; Goldberg, Avi; Levy, Chezy; Hochman, Ohad; Kassem, Sameer; Attias, Samuel (Frontiers in Medicine, 2025)
BackgroundPromoting the resilience of healthcare providers (HCP) is crucial during peaceful times and even more during national crisis. The outbreak of the war in Israel, Gaza strip, and Lebanon in October 2023 prompted the establishment of integrative medicine resilience clinics (IMRC) in three hospitals; incorporating evidence based integrative medicine (IM) modalities, for reducing emotional and physical concerns among HCP. Our objective was to explore the impact of the IMRC through narratives of IM practitioners who provided the treatments. To explore the impact of the IMRC through narratives of IM practitioners who provided the treatments.MethodsQualitative narrative research was based on in-depth interviews with 16 IM practitioners from IMRC’s in three hospitals.ResultsThe interviewees’ narratives revealed four spheres where the IMRC’s contribution is suggested: 1- IM practitioners conceived their work to be effective in improving HCP wellbeing; 2- they felt that HCP functioned more effectively and provided better patient care; 3- practitioners described feeling meaningful, and acknowledged in the healthcare organization; 4- the positive impact of IM on HCP and administrators, positions them as potential advocates for IM in public health.ConclusionIMRC for hospital HCP may have an important role in maintaining HCP resilience during wartime. These effects may also have ramifications on the recognition of the role of IM in public health during crisis and everyday times.